The Development of Free Inquiry Lab-Based Students’ Worksheet to Increase the Dimension in Science Literacy Process - Heleri, Heleri; Situmorang, Risya Pramana; Dewi, Lusiawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2019)
This research aimed at 1) developing and producing feasible free inquiry lab-based students’ worksheet to increase the dimension in students’ science literacy process and 2) examining the effectivity of free inquiry lab-based students’ worksheet in increasing the dimension in students’ science literacy process. This research was conducted using research and development method. The students of XI MIPA SMA Kristen 1 Salatiga were the subject of this research. This research was conducted in the first semester of 2018-2019 academic year. The validation questionnaire and students’ response, the observation sheet of dimension process and learning model implementation, and science literacy question sheet were the research instrument covered in this research. The hypothesis test was conducted using paired-sample t-test. The result of this research revealed that 1) the developed free inquiry lab-based students’ worksheet was feasible based on the assessment result from the professional validator with the average 80.19% and the students’ response was very good towards the worksheet with the assessment average 82.49%. 2) The free-inquiry lab students’ worksheet was effective in increasing students’ dimension in science literacy process in plant tissue topic, which was supported with the average of students’ dimension of science literacy process 87.71% (very good) and the students’ N-Gain was 0.7 (very good). It was proved by the paired samples t-test statistic test with the result 0.00 < 0,05, therefore H0 was rejected, or in the other words, the free inquiry lab-based students’ worksheet was effective in increasing the dimension in science literacy process.